2012
DOI: 10.1111/mec.12140
|View full text |Cite
|
Sign up to set email alerts
|

Global genetic analysis reveals the putative native source of the invasive termite, Reticulitermes flavipes, in France

Abstract: Biological invasions are recognized as a major threat to both natural and managed ecosystems. Phylogeographic and population genetic analyses can provide information about the geographical origins and patterns of introduction and explain the causes and mechanisms by which introduced species have become successful invaders. Reticulitermes flavipes is a North American subterranean termite that has been introduced into several areas, including France where introduced populations have become invasive. To identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 56 publications
3
61
1
Order By: Relevance
“…Indeed, it was later shown that R. santonensis had been misidentified; the "species" turned out to be R. flavipes, which had become established in France (and other parts of the world) after several of its founders had arrived from Louisiana, most likely when it was still a French colony (Perdereau et al 2010b(Perdereau et al , 2011(Perdereau et al , 2013. The CHC data confirm the DNA data.…”
Section: The Multifaceted Roles Of Cuticular Hydrocarbons In Recognitionmentioning
confidence: 63%
“…Indeed, it was later shown that R. santonensis had been misidentified; the "species" turned out to be R. flavipes, which had become established in France (and other parts of the world) after several of its founders had arrived from Louisiana, most likely when it was still a French colony (Perdereau et al 2010b(Perdereau et al , 2011(Perdereau et al , 2013. The CHC data confirm the DNA data.…”
Section: The Multifaceted Roles Of Cuticular Hydrocarbons In Recognitionmentioning
confidence: 63%
“…2005; Perdereau et al. 2010, 2013). The amplification of all primers was performed using a Stratagene thermal cycler in accordance with Vargo (2000), except for the following minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…This makes it difficult to determine which result is the most likely when several alternatives are proposed . However, these classical and Bayesian methods have proved both useful and conclusive in other cases of invasion (Ciosi et al 2008;Facon et al 2003;Kolbe et al 2004;Papura et al 2012;Perdereau et al 2013;Wan et al 2012). We can therefore put forward several hypotheses to account for the conflicting results obtained here: (1) the low level of diversity may have resulted in a lack of power to discriminate between the two possible alternatives, (2) the strong spatial genetic structure observed in the USA, requiring a very large sampling scheme to embrace most genetic variation of the native and (3) the lack of samples from some of the existing invaded areas, such as China or South Korea, potentially serving as sources for the invasion of Europe, as suggested by Figueiredo et al (2013) on the basis of analyses of collection samples for PWN.…”
Section: Very Low Levels Of Polymorphism In Invaded Areasmentioning
confidence: 99%
“…Deciphering geographic pathways followed by invasive species is a key first step in this direction. Many studies carried out over the last decade have tried to identify the invasion routes of several invasive species, including insects (Papura et al 2012;Pascual et al 2007;Perdereau et al 2013;Zepeda-Paulo et al 2010), plants (Kelager et al 2013), nematodes (Boucher et al 2013) and fungi (Fontaine et al 2013). Indeed, this approach can be used to address various questions of both practical and theoretical concern .…”
Section: Introductionmentioning
confidence: 99%